Spatial Variation in Vegetation Carbon Stock in Forest Ecosystems of Rajasthan, India - Singh, G.; Mishra, D.; Singh, K.; Shukla, Smita; Bala, N. (Indian Forester, 2019)
The extent and distribution of dry forests play an important role in biodiversity conservation and carbon storage. Field measurements were carried out during 2008-2012 at 903 sampling plots in forests of 33 districts of Rajasthan and carbon stock due to trees, shrubs, bamboos, tree saplings, herbaceous vegetation and dead material (litter and coarse woody debris - CWD) were estimated for their spatial variation and to devise a programme of reforestation. There were significant (P<0.05) differences in carbon stock ranging from 0.02-0.91 tons ha-1 for litter, 0.00- 0.39 tons C ha-1 for CWD, 0.005-0.84 tons ha-1 for herbaceous biomass, 0.09-5.22 tons ha-1 for shrubs, 1.17-13.96 tons ha-1 for trees, 0.00-0.29 tons ha-1 for bamboo and 0.01-0.26 tons ha-1 for tree saplings. The variations were found to relate to rainfall pattern. Highest values were in Kota, Karauli, Rajasamand, Pratapgarh, Udaipur and Dungarpur respectively. Contribution of trees, shrubs, bamboos and sapling were 85.5%, 13.0%, 0.39% and 1.30%, respectively signifying the role of trees in terrestrial carbon storage. Lowest carbon stock was in Churu (0.051 million tons) and highest in Udaipur (8.079 million tons) out of total standing carbon stock, wherein 27.31 million tons was above-ground and 11.68 million tons was in root biomass in forests of Rajasthan. Strong spatial variations in component-wise carbon stock and below state average standing carbon stock in almost 15 districts in Rajasthan suggests taking up forest management by enrichment tree planting for increasing diversity and productivity leading to increased carbon sequestration and climate change mitigation.